The Race Between Deterrence and Displacement: Theory and Evidence from Bank Robberies - Maheshri, Vikram; Mastrobuoni, Giovanni (The Review of Economics and Statistics, 2021)
Abstract Security measures that deter crime may unwittingly displace it to neighboring areas, but evidence of displacement is scarce. We exploit precise information on the timing and locations of all Italian bank robberies and security guard hirings over a decade to estimate deterrence and displacement effects of guards. A guard lowers the likelihood a bank is robbed by 35% to 40%. Over half of this reduction is displaced to nearby unguarded banks. Theory suggests optimal policy to mitigate this spillover is ambiguous. Our findings indicate restricting guards in sparse, rural markets and requiring guards in dense, urban markets could be socially beneficial.